Analisis Kesulitan Mahasiswa dalam Menyelesaikan Soal pada Materi Pertidaksamaan dan Fungsi Limit - Deby Erdriani; Dewi Devita (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
The research is aimed to analyze students’ difficulties in studying calculus on inequality and limitfunction in Calculus subject. The research is qualitatively analyzed using descriptive data taken inacademic year of 2018/2019 at the University of Putra Indonesia YPTK, Padang. The subject of the research is53 students majoring in Computer System. The samples are 6 students grouped into 2 high-grade students, 2middle-grade students and 2 low-grade students. Each class taken has already represented the average scores.The research is done in February until April 2019. The data are collected through documentation and interview.The result of the research shows some factors which cause mistakes the students did in Calculus subject,namely 1) student’s inability to perform mixed fraction, 2) student’s inability to use theorems in case ofinequality in absolute values. 3) student’s inability to seek factorization in many rates and 4) student’sinability to do limit function operation in polynomial fraction.